2010
DOI: 10.1021/bm901331t
|View full text |Cite
|
Sign up to set email alerts
|

Study of Aliphatic-Aromatic Copolyester Degradation in Sandy Soil and Its Ecotoxicological Impact

Abstract: Degradation of poly[(1,4-butylene terephthalate)-co-(1,4-butylene adipate)] (Ecoflex, BTA) monofilaments (rods) in standardized sandy soil was investigated. Changes in the microstructure and chemical composition distribution of the degraded BTA samples were evaluated and changes in the pH and salinity of postdegradation soil, as well as the soil phytotoxicity impact of the degradation products, are reported. A macroscopic and microscopic evaluation of the surface of BTA rod samples after specified periods of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
54
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 41 publications
5
54
0
Order By: Relevance
“…The biodegradability has been intensively evaluated by many authors [2-4, 7, 8]. The thermal properties of the polymer composition have been studied by means of DSC [5], and the general structures and composition information have been investigated by using NMR and GC-MS [8][9][10]. Many researchers [6,[11][12][13] have also demonstrated that the copolyester structure (random or block) can be investigated using multistage mass spectrometry (MS n ) with various soft ionization techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The biodegradability has been intensively evaluated by many authors [2-4, 7, 8]. The thermal properties of the polymer composition have been studied by means of DSC [5], and the general structures and composition information have been investigated by using NMR and GC-MS [8][9][10]. Many researchers [6,[11][12][13] have also demonstrated that the copolyester structure (random or block) can be investigated using multistage mass spectrometry (MS n ) with various soft ionization techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Ecotoxicity tests based on plants growth (such as oat, cress, radish, etc.) also demonstrated that degradation products are totally harmless to the tested plants [7]. Meeting the requirements, Ecoflex has thus been certified as compostable material.…”
mentioning
confidence: 78%
“…The highest C ha concentrations were assessed in alkaline extracts obtained from composts without nonwoven fabric supplement (K0). On the other hand, Richter et al [16] report enzymatic character of BTA degradation with a small share of hydrolysis processes and the fact that the higher the share of aromatic rings, the more difficult the microbial decomposition [4].…”
Section: Humic Compoundsmentioning
confidence: 99%
“…The type of organic matter used for the composting process, the quantity and kind of added polymer material also have an influence on these properties. It is important because the biodegradation process of some plastics is much faster in the "natural" environment than in simulated laboratory conditions [8] and it does not show an ecotoxic effect [16][17][18]. Humification process which occurred in the materials composted with a small amount of biodegradable materials is progressing similarly as humification process of organic matter supplied to the soil with organic fertilizers or other organic materials [19].…”
Section: Humic Compoundsmentioning
confidence: 99%